The interaction between training and change in South African organisations - Miemie Struwig; Elroy Smith; Danie Venter (South African Journal of Business Management, 2000)
This article outlines the results of a study which investigates the interaction between training and change in South African organisations. A literature study provides a theoretical foundation which explains the nature of the interaction between training an change in the organisation. An empirical survey was conducted, using a self-administered questionnaire which was sent to 365 training practitioners to test six null-hypotheses. To prove the stated hypotheses, specific statistical methods, such as analysis of variance and correlation coefficients, are used. The results showed highly significant relationships between training and organisational change variables (one of the null-hypotheses was rejected). The results indicated that management should use training to facilitate change in the organisation. This, however, requires a shift in emphasis regarding the traditional role of training in the organisation. Training should be placed at the centre of human resources practices and the strategic plans of the organisation.
Keywords: 650